(Des)teço-me ao professorar : entre linhas formativas e trapilhos da Educação em Ciências - Oliveira, Caroline Barroncas de (2020)
(En) Weaved by teaching, influenced by ongoing (or not) experiences, allowed an investigation to be resized, to become a twist of different views which was embodied in the following problem: How can the narrative of autobiographical formative episodes by a teacher-trainer contribute to new / other ways of thinking and acting in teacher education processes that teach science ?. I went back to my own academic training history, understand how the narrative of autobiographical episodes of a teacher-trainer can contribute to new / other ways of thinking and acting in teacher education processes that teach Science. As unfolding, here are the following applicable goals: Narrating the epistemic and existential episodes that tensioned my formative path as a teacher-trainer in Science Education; To know that training and teaching experiences lived by me can indicate ways for the formation of the teacher who teaches science from the perspective of investigating his own practice; Demonstrate how my narrative training experience can make more visible and further enhance different dimensions of my training path in alternative training ideas. In thesis, assume that: An autobiographical narrative, from an epistemological investigation perspective, when anchored in a rationality that embraces various knowledeges centered on life itself, mobilizing alternative formative experiences in Science Education. In order to narrate the autobiographical data, I used the logbook, research reports, academic memorial, letter writing, various documents, among other methodological devices. The movement starts from the field of teacher (self)education, assuming that that the writing of the possibility or the self-knowledge of the teacher-trainer. Through this moving tracking I (de) build myself before life choices, the relations that it creates with Science Education itself and places me in constant search of knowing-living from the creation of alternative training ideas through inventive experiments to the teacher.